2013
DOI: 10.1016/j.neuroimage.2013.05.063
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–temporal atlas of human fetal brain development during the early second trimester

Abstract: During the second trimester, the human fetal brain undergoes numerous changes that lead to substantial variation in the neonatal in terms of its morphology and tissue types. As fetal MRI is more and more widely used for studying the human brain development during this period, a spatiotemporal atlas becomes necessary for characterizing the dynamic structural changes. In this study, 34 postmortem human fetal brains with gestational ages ranging from 15 to 22 weeks were scanned using 7.0 T MR. We used automated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 76 publications
3
44
0
Order By: Relevance
“…Fetal brains showed a higher volumetric growth in the frontal and temporal lobes with a major anterior-to-posterior directional stretch during 15–22 gestational weeks32. Greater volume increases in the parietal and occipital regions compared to the frontal lobes33 were observed during 20–28 gestational weeks.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Fetal brains showed a higher volumetric growth in the frontal and temporal lobes with a major anterior-to-posterior directional stretch during 15–22 gestational weeks32. Greater volume increases in the parietal and occipital regions compared to the frontal lobes33 were observed during 20–28 gestational weeks.…”
Section: Discussionmentioning
confidence: 95%
“…1). Interestingly, while the fetal brain showed volumetric contraction in the lateral ventricle in the second trimester, possibly due to increase in the thickness of the cortical mantle relative to the ventricles32, the infant brain shows the most active ventricular growth during the first year of life13.…”
Section: Discussionmentioning
confidence: 99%
“…41 human fetuses (13 males and 28 females) with a gestational age (GA) of 14 to 22 weeks, which were partially used to study brain development characteristics at the 20th gestational week (GW), subcortical brain structures, cortical folding, and the fetal brain template in previous publications (Zhang et al, 2010, 2011; Meng et al, 2012; Zhan et al, 2013), were included in the study. All fetuses were collected in hospitals of Shandong Province, China.…”
Section: Methodsmentioning
confidence: 99%
“…The establishment of human cognitive abilities is a gradual process that takes place mostly in the period between birth and adulthood, although some developmental processes extend beyond this period (Sowell et al, 2004; Thompson et al, 2004; Zhan et al, 2013). During this time window, the brain undergoes dramatic molecular transformations, which are manifested both structurally and functionally (de Graaf-Peters and Hadders-Algra, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…During this time window, the brain undergoes dramatic molecular transformations, which are manifested both structurally and functionally (de Graaf-Peters and Hadders-Algra, 2006). Notably, shortly after the brain development is accomplished, the process of brain aging commences at early adulthood, which is revealed by the gradual decline of the brain ability to absorb and process the flow of information (Sowell et al, 2004; Peters et al, 2008; Salthouse, 2009; May, 2011; Zhan et al, 2013). However, more recent research has revealed that changes in brain circuits are not exclusively restricted to the early stages of brain development, and has supported the concept of continuous neuroplasticity throughout live (May, 2011; Taubert et al, 2012).…”
Section: Introductionmentioning
confidence: 99%